MANAGEMENT FOR GAPOKTANHUT LESTARI SEJAHTERA: INITIAL OPTIMIZATION ON ROBUSTA COFFEE DNA AMPLIFICATION FOR MOLECULAR SPECIES CONFIRMATION - Elly Lestari Rustiati; Priyambodo; Dian Neli Pratiwi; Eko Agus Srihanto; Muhammad Febriansyah; Andri Wijaya Kusuma; Enny Saswiyanti; Alvin Wiwiet Susanto (BIOVALENTIA: Biological Research Journal, 2024)
Gapoktanhut Lestari Sejahtera, a community engaged in coffee plantation practices within the community forests of the Forest Protection of Register 31 Pematang Arahan, Tanggamus, operates under the forest management unit, KPH Kotaagung Utara, Tanggamus, Lampung.  In line with its commitment to biodiversity governance and the preservation and conservation of forest biodiversity, species confirmation, particularly for its robusta coffee, is deemed necessary. A leaf-based molecular species confirmation was proposed, a method yet to be conducted in Lampung.  Therefore, prior to its molecular analysis, a preliminary study focusing on temperature optimization for robusta coffee DNA extraction for species confirmation was undertaken. This study was conducted under the DIPA BLU Unila Basic Research Grant in 2023, in collaboration with the Biotechnology Laboratory, Lampung Disease Investigation Center.  Robusta coffee leaves were sampled from six forest farmer groups, KTH Bumi Mulyo, Sido Makmur 1, Sido Makmur 2, Sido Makmur 3, Mandiri Jaya, and Murah Rejeki 1, in collaboration with Gapoktanhut Lestari Sejahtera, Semaka, Tanggamus. The DNA extraction process adhered to the Genomic DNA Mini Kit (Plant) protocol (ISO 9001: 2008 QMS). DNA amplification was performed using the Polymerase Chain Reaction (PCR) method, utilizing the Coffea N-methyltransferases gene marker primer.  The DNA analysis on robusta coffee leaf samples from Gapoktanhut Lestari Sejahtera demonstrated a good presence of DNA with an amplification temperature of 55°-60°C. To advance to the subsequent process, optimization of DNA extraction is required to yield improved results.